Allergic contact dermatitis from dicyclohexylmethane-4,4 '-diisocyanate - Engfeldt, Malin; Björkner, Bert; Hamnerius, N; Zimerson, Erik (Contact Dermatitis, 2003)
From August 1999 to April 2001, there was an outbreak of severe eczema at a factory manufacturing medical equipment. A glue, mainly based on the isocyanate dicyclohexylmethane-4,4'-diisocyanate (DMDI), was suspected as being the cause of the problem. 16 workers with recent episodes of eczema were patch tested with a standard series, an isocyanate series and work material. The latter consisted of, among other things, the glue, DMDI, and an amine, dicyclohexylmethane-4,4'-diamine (DMDA), which is formed when DMDI reacts with water. 13 patients reacted to DMDI, 9 to 1,6-hamethylenediisocyanate (HDI) and 4 to isophoronediisocyanate (IPDI), all of which are aliphatic isocyanates. None reacted to the aromatic isocyanates, diphenylmethane-4,4'-diisocyanate (MDI) or toluenediisocyanate (TDI). One explanation for this pattern could be that aromatic diisocyanates are more reactive than the aliphatic ones and that, therefore, they are inactivated before penetrating the skin. 5 patients reacted to DMDA and 5 to 4,4-diaminodiphenylmethane (MDA). Concurrent reactions to DMDA and or MDA with DMDI could be due to cross-reactivity. The positive reactions to MDA could also be a marker of MDI exposure. Yet another patient, investigated in 1997 with suspected work-related contact dermatitis from the glue, is described. She, however, showed no positive reactions to any isocyanates.
The information about affiliations in this record was updated in December 2015. The record was previously connected to the following departments: Pediatrics/Urology/Gynecology/Endocrinology (013240400), Occupational and Environmental Dermatology Unit (013241310)
Keywords: polyurethane; occupational; methylenebis(4-cyclohexylisocyanate); DMDI; contact allergy; CAS 5124-30-1; CAS 1761-71-3; 4 ' diisocyanate; dicyclohexylmethane-4; allergic contact dermatitis